PENGARUH KEPADATAN TANAH TERHADAP BESARNYA HARGA DRAFT SPESIFIK PEMBAJAKAN TANAH - , ARI ANDRI YASTOMO, Ir. Sunarto Ciptohadidjoyo, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The specific draft of tillage is the mechanical characteristic of soil are strongly associated with the magnitude of the force to cultivate the land. Value of specific draft tillage will determine the amount of power required of tillage. The previous research indicate that there is a relation between the value of specific draft tillage with soil moisture content. This research aims to determine the effect of soil density to the specific draft with moldboard plow. The research was conducted in various soil densities that were 3.15 kg/cm2, 3.75 kg/cm2, 4.71 kg/cm2, 6.12 kg/cm2 and 7.39 kg/cm2. The soil used in this research was regosol soil which taken from the Village Wirokerten, Banguntapan District, Bantul Regency and has a percentage of silt by 23,90%, clay 15, 27%, and the sands of 60,82%. The parameters observed were force / load (kg) and values ofcone index (kg/cm2). The results showed that soil density had significantly effect the value of specific draft tillage. The specific draft tillage will be higher with increasing soil density. The relation of specific draft and soil density is y = 0.0323x+0.1148 with y is the value of a specific draft tillage and x is the value of soil cone index